2021
DOI: 10.2106/jbjs.cc.21.00271
|View full text |Cite
|
Sign up to set email alerts
|

Novel Utilization of Anterior Intrapelvic (Stoppa) Approach for Periacetabular Ganz Osteotomy

Abstract: Case: The Ganz periacetabular osteotomy (PAO) is widely used to correct developmental hip dysplasia in the adolescent and young adult population. The aim of this case study was to examine the novel utility and safety of Stoppa approach for the Ganz PAO in a 15-year-old girl and 25-year-old man. The Stoppa approach is traditionally used for acetabular fractures, and its use for a Ganz PAO is relatively novel. Conclusion: The Stoppa approach allows surgeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Utilizing modified Stoppa approach for PAO is infrequently discussed in literature. Klahs et al [ 34 ] reported 2 cases where they utilized modified Stoppa approach for PAO and demonstrated the same benefits of enhanced visualization and reduced X-ray exposure. They recommended the utilization of the novel radiolucent retractors to provide adequate soft-tissue protection and not inhibiting the fluoroscopic with additional light source and suction port.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing modified Stoppa approach for PAO is infrequently discussed in literature. Klahs et al [ 34 ] reported 2 cases where they utilized modified Stoppa approach for PAO and demonstrated the same benefits of enhanced visualization and reduced X-ray exposure. They recommended the utilization of the novel radiolucent retractors to provide adequate soft-tissue protection and not inhibiting the fluoroscopic with additional light source and suction port.…”
Section: Discussionmentioning
confidence: 99%